COENZYME Q10 TREATMENTS INFLUENCE THE LIFESPAN AND KEY BIOCHEMICAL RESISTANCE SYSTEMS IN THE HONEYBEE, Apis mellifera. Issue 3 (21st March 2014) - Strachecka, Aneta; Olszewski, Krzysztof; Paleolog, Jerzy; Borsuk, Grzegorz; Bajda, Milena; Krauze, Magdalena; Merska, Malwina; Chobotow, Jacek
<x xml:space="preserve">Abstract</x> Natural bioactive preparations that will boost apian resistance, aid body detoxification, or fight crucial bee diseases are in demand. Therefore, we examined the influence of coenzyme Q10 (CoQ10, 2, 3‐dimethoxy, 5‐methyl, 6‐decaprenyl benzoquinone) treatment on honeybee lifespan, Nosema resistance, the activity/concentration of antioxidants, proteases and protease inhibitors, and biomarkers. CoQ10 slows age‐related metabolic processes. Workers that consumed CoQ10 lived longer than untreated controls and were less infested with Nosema spp. Relative to controls, the CoQ10‐treated workers had higher protein concentrations that increased with age but then they decreased in older bees. CoQ10 treatments increased the activities of antioxidant enzymes (superoxide dismutase, GPx, catalase, glutathione S‐transferase), protease inhibitors, biomarkers (aspartate aminotransferase, alkaline phosphatase, alanine aminotransferase), the total antioxidant potential level, and concentrations of uric acid and creatinine. The activities of acidic, neutral, and alkaline proteases, and concentrations of albumin and urea were lower in the bees that were administered CoQ10. CoQ10 could be taken into consideration as a natural diet supplement in early spring before pollen sources become available in the temperate Central European climate. A response to CoQ10 administration that is similar to mammals supports our view that Apis mellifera is a model organism for biochemical gerontology.